Microarray Analysis of Antigen-Dependent B-Cell Activation Gene Expression in Bitches with Pyometra. (September 2014) - Bukowska, D.; Kempisty, B.; Zawierucha, P.; Ciesiółka, S.; Piotrowska, H.; Jopek, K.; Antosik, P.; Brüssow, K.P.; Nowicki, M.; Bruska, M.; Zabel, M.; Jaśkowski, J.M.
Canine pyometra is defined as a complex disease associated with activation and proliferation of immune specific cells, B and T cells, as well as synthesis and activation of immune and pro-inflammatory molecules. Although all of these mechanisms are well recognized in several human immune diseases and cancers, the possible role or dysfunction of these molecules in dogs with pyometra still requires investigation. This study was aimed to examine antigen-dependent B-cell activation gene expression (CD4, CD28, CD40, CD80, Fas, HLA-DRB1 and IL10) in a total of 24 mixed-breed bitch uteri with pyometra and 20 healthy controls. Using canine RNA microarray assays (Affymetrix) altogether 17, 138 different transcripts were analyzed. A significant increase was found of CD28, CD40, HLA-DRB1 (P<0.001), and CD4, CD80, Fas and IL10 (P<0.01) in the group of bitches with pyometra, as compared to controls. In the affected group an increased share of CD4, CD28, CD40, CD80, Fas, HLA-DRB1 and IL10, (13.6-, 2.8-, 2.9-, 5.6-, 3.3-, 4.4-, and 6.5-fold increase, respectively) was also detected. It is suggested that an increased expression of B cell-specific immune response molecules may be associated with recruitment of immunologically specific cells in bitches with pyometra as well as with activation of pro-inflammatory proteins as a consequence of exposure to foreign antigens due to bacterial infection.